Comparison of different lipid extraction methods for roots of barley - Reyna, M. (2020)
The plant lipidome is highly complex, and the composition of lipids in different tissues as well as their specific functions in plant development, growth and stress responses have yet to be fully elucidated. To do this, efficient lipid extraction protocols which deliver target compounds in solution at concentrations adequate for subsequent detection, quantitation and analysis through spectroscopic methods are required. To date, numerous methods are used to extract lipids from plant tissues. However, a comprehensive analysis of the efficiency and reproducibility of these methods to extract multiple lipid classes from roots of barley has not been undertaken. In this study, we report the comparison of three different lipid extraction procedures in order to determine the most effective lipid extraction protocol to extract lipids from root tissues of the Barley linked to a lipidomicsbased ESI-MS/MS assay coupled with a statistical analysis. While particular methods were best suited to extract different lipid classes from barley roots, overall a single-step extraction method with a 24 h extraction period, which uses a mixture of chloroform, isopropanol, methanol and water, was the most efficient, reproducible and the least labor-intensive to extract a broad range of lipids for untargeted lipidomic analysis of Barley roots. In addition, the optimal protocol for barley root lipid extraction involves immediately submerging plant tissues in hot isopropanol containing 0.01% BHT right upon harvesting of fresh tissues from their respective culturing conditions, which will produce undistorted lipid profiles truly reflective of the endogenous levels of phosphatidylcholine and phosphatidic acid molecular forms (PCs and PAs). Given the critical role of PCs as predominant membrane lipids, as well as the established function of PAs as signal lipid, it is evident that strict adherence to sample pre-treatment protocol is indispensable in deriving biologically meaningful lipid profiles in plants. On the other hands, results indicate that the use of the simplified method allows improving the extraction performance of acidic lipids (PA and phosphatidylserine), which is reflected in a significant increase in the lipid content. Moreover, the data variability obtained by new method extraction was higher than classic method. However, the relation between the amount of extracted lipids and data variability was lower with a single-step extraction method suggesting this extraction could generate a lipid profiles closer to the real composition of the analyzed tissue.